1994
DOI: 10.1093/ee/23.1.136
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the Whitefly Predator Delphastus pusillus (Coleoptera: Coccinellidae) with Parasitized Sweetpotato Whitefly (Homoptera: Aleyrodidae)

Abstract: Delphastus pusillus (LeConte), an indigenous coccinellid predator of whiteflies, including sweetpotato whitefly, Bemisia tabaci (Gennadius), feeds on all stages of whiteflies. In laboratory tests, fourth-instar and adult female D. pusillus exhibited a marked tendency to avoid fourth-instar B. tabaci parasitized by the aphelinid endoparasitoids Encarsia tmnsvena (Timberlake) and Eretmacerus sp. nr. calif amicus Howard in favor of unparasitized whiteflies. The age of the parasitoid within the whitefly influenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 7 publications
(9 reference statements)
3
44
1
Order By: Relevance
“…Although nutritional, chemical and morphological changes in plants have been reported to affect whitefly population in tomato, beans, and zucchini (Noortje & Lindhout, 1992;Hooks et al, 1998;Leite et al, 1998), leaf N and K, chemical compounds analyzed and trichomes were apparently not important in this study. The trichomes (% non-glandular) found in okra were of low density and did not contain toxic compounds, which could affect oviposition and present antibiotic effects.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…Although nutritional, chemical and morphological changes in plants have been reported to affect whitefly population in tomato, beans, and zucchini (Noortje & Lindhout, 1992;Hooks et al, 1998;Leite et al, 1998), leaf N and K, chemical compounds analyzed and trichomes were apparently not important in this study. The trichomes (% non-glandular) found in okra were of low density and did not contain toxic compounds, which could affect oviposition and present antibiotic effects.…”
Section: Resultsmentioning
confidence: 55%
“…in September. These natural enemies have been used to control whitefly population in several plants (Legaspi et al, 1996a(Legaspi et al, , 1996bLiu & Stansly, 1996a and, in some cases, a positive effect was obtained (Hoelmer et al, 1994;Heinz & Nelson, 1996). Hooks et al (1998) reported high populations of coccinellids and syrphids in zucchini plants infested with high populations of aphids and whiteflies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chrysoperla carnea larvae readily fed upon immature E. transvena within 4th instar B. tabaci in laboratory assays (Kapadia and Puri, 1990). Adult Delphastus pusillus did not differentiate between unparasitized B. tabaci and those parasitized with young E. transvena, but both adults and larvae avoided older larval and pupal stages in laboratory studies (Hoelmer et al, 1994). The impact of these examples of intraguild predation on biological control of B. tabaci in the field are largely unknown.…”
Section: Other Disruptive Factorsmentioning
confidence: 96%
“…The beetles would starve if only scales containing pupae of this parasitic fl y were available (Quezada & de Bach 1973 ). Delphastus pusillus , a predator of all stages of whitefl ies, exhibited a marked tendency to avoid fourth instar Bemisia tabaci containing third instar and pupal aphelinid endoparasitoids (Hoelmer et al 1994 ).…”
Section: Prey F Eeding On R Esistant P Lantsmentioning
confidence: 99%